Streptococcus salivarius meningitis after spinal anaesthetic. Issue 2 (17th August 2014) - Messing, Jonathan
Summary: Meningitis following spinal anaesthesia is a recognised but rare complication. In this case, an uncommon pathogen is described causing severe meningitis, and became symptomatic within 17 hours of the spinal. Although the pathogen can be treated with standard therapy resulting in no long term neurological sequelae it raises questions regarding the wearing of face masks by staff in order to prevent contamination of both the site of lumbar puncture and the laboratory sample.